AN ANALYTICAL STUDY OF ECONOMIC FACTORS AFFECTING THE DEVELOPMENT OF VIDARBHACHAYA - Sadar, Bhavana Gajanan; Joshi, Dr. Parag (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Vidarbha, located in the eastern part of Maharashtra, presents a surprisingly confusing story. This region, blessed with fertile land and abundant natural resources, stands in stark contrast to the state’s thriving economic scenario. For this reason, the present research explores the complexities that have led Vidarbha to a state of persistent economic backwardness. The agricultural sector, which is the lifeblood of the region, is plagued by insecurity. Over-reliance on rain-fed agriculture, especially cotton cultivation, leaves farmers exposed to the vagaries of nature. Irregular rainfall, volatile market prices, create a vicious cycle of debt and despair, with heartbreaking consequences – a grim reality illustrated by the tragic rise in farmer suicides. Beyond the agricultural sector, Vidarbha’s economic stagnation is due to multiple factors. Inadequate infrastructure, including limited irrigation facilities and poor roads, hamper economic growth and limit market access. The region also lags behind western Maharashtra in industrial development. The lack of small and medium enterprises (SMEs), an important source of employment, further diminishes economic opportunities for the population. Moreover, allegations of nepotism by the state government raise concerns about inadequate investment and development policies designed to meet the specific needs of Vidarbha. This perception underscores the sense of neglect that perpetuates Vidarbha’s economic disadvantage. This research study provides an analytical study of the economic factors influencing Vidarbha’s development.